A Qualitative Study on Migrant Labourers in Idukki District, Kerala - Jijo James Indiparambil (Selected Topics in Humanities and Social Sciences Vol. 4, 2021)
Migration is viewed as an important livelihood strategy for poor groups across the world. It cannot be reduced to merely an immediate response to challenges and issues in a given situation of the country or place of origin. Migrant labourers have become a significant economic force in India. The Kerala State in India witnesses a large influx of migrant workers from different parts of the country, especially from West Bengal, Tripura, Assam, Bihar, Uttar Pradesh, Odisha, Maharashtra and Tamil Nadu. The outmigration from Kerala to abroad due to the higher education opportunities and qualifications and the scarcity of unskilled/semiskilled workers within the State as well as the higher employment opportunities with fair salary and life situations and non-discriminatory attitudinal and behavioural pattern of its people amplify this internal relocation to Kerala. The main objective of this study is to examine the present and future implications of large scale interstate migration in rural areas. This study on inter-state migration in Kerala sheds light on the various issues concerning migration, mobility, and sustenance, based on a sample survey of 140 households in Idukki District as well as on literature reviews. It examines the diaspora situation, i.e., migration dynamics from multiple perspectives including demographic, economic and socio-political aspects. It is a qualitative analytical study on inter-state diaspora in Kerala.